(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Brain tumors (BT) are a highly heterogeneous group of neoplasms that differ in their molecular characteristics, clinical manifestations, therapeutic approaches, and survival prognosis [1]. The pathophysiology of BTs is determined by multiple factors, including their origin (primary or secondary tumors), microenvironmental features, vascular architecture, and individual patient characteristics [2,3]. Tumor metabolism is known to be closely linked to vascular function and morphology, which is reflected in the pattern of contrast enhancement during neuroimaging [4].